Hubungan Dukungan Keluarga dengan Tingkat Harga Diri pada Penderita Stroke di Rumah Sakit Umum Royal Prima Medan - Yusmawarnita Zai; Kandrinus Bu’ulolo; Novy Fajariani; Yasozatulo Hulu; Ruslan Efendi Gulo; Eva Latifah Nurhayati (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
Stroke is a condition where a part of the brain is suddenly disturbed which is caused by a lack of blood supply, which causes an inhibition of metabolic processes. As a result of a stroke affects the psychological function of the patient, so the patient feels his level of self-esteem decreases or is low. The role and support of families play an important role in the rehabilitation process to provide health services for stroke patients. The aim is to find out the relationship of family support with the level of self esteem (self-esteem) in stroke patients at the Royal Prima Medan Hospital in 2019. The design used a